Toward Indication-Stratified Local Reference Levels for IGRT Cone-Beam CT: A Clinical Audit of CTDIvol and DLP Across Ten Workflows on Versa HD - O. El Mouden; H. Sekkat; A. Bannan; F. Chaara; H. Bendouro; R. El Baydaoui; M. Bougteb; M. Tahiri; O. El rhazouani; Y. Berrada; M. Mkimel (Health Physics, 2026)
To characterize routine kV cone-beam CT (CBCT) imaging dose in image-guided radiotherapy (IGRT) and to derive indication-specific local benchmark values using and DLP for clinical protocol optimization. This retrospective single-center audit included 300 CBCT examinations acquired on a Versa HD linear accelerator (Elekta AB, Stockholm, Sweden) using XVI v5.0.4. Examinations were grouped into 10 clinical indication workflows. For each CBCT, acquisition descriptors (CTDI phantom, kVp, total mAs, scan arc, FOV, bowtie, scan length) and dose indices were extracted. (mGy) was analyzed as recorded (reference value). DLP (mGy cm -1 ) was derived/verified as × scan length. Indication-stratified distributions were summarized using mean ± SD and 95% CI, with examination-level visualisation. An optional parameter-based estimation model ( ) was evaluated as a quality-control layer using Bland–Altman analysis. Across all examinations, was 3.25 ± 3.06 mGy (range 0.123–10.109) with median 1.44 mGy (IQR 0.84–5.96). DLP was 80.27 ± 75.66 mGy cm -1 (range 2.21–255.81) with median 34.36 mGy cm -1 (IQR 18.55–150.38). Dose indices differed markedly by indication (≈49-fold between lowest and highest mean ). The highest mean occurred for Prostate IGRT (7.69 ± 1.95 mGy) and Pelvic nodes (7.21 ± 1.83 mGy), whereas Extremity setup (0.156 ± 0.027 mGy) and Brain SRS/SRT (0.263 ± 0.062 mGy) were the lowest. DLP was highest for Pelvic nodes (187.6 ± 47.5 mGy cm -1 ) and Prostate IGRT (169.1 ± 42.9 mGy cm -1 ). The estimation model showed minimal bias (Bland–Altman bias 0.007 mGy; 95% limits of agreement −0.321 to 0.335 mGy). Routine IGRT CBCT dose on Versa HD/XVI shows strong indication dependence, driven by protocol selection and scan extent. The reported indication-resolved /DLP distributions provide a practical basis for local reference levels and targeted optimization of high-dose workflows (pelvic/abdominal) while preserving low-dose protocols for cranial/extremity indications.